PENGEMBANGAN PRODUK HYBRID CONTRACT DALAM PERBANKAN SYARIAH - Aulia Putri Putri; Fazna Anggia Muslimah; Jihan Luthfi Arwana; Husni Kamal (STAI La Tansa Mashiro, 2026)
The development of the Islamic banking industry requires continuous product innovation to meet the growing demands of modern financial transactions while maintaining compliance with Sharia principles. One of the innovations that has gained significant attention is the hybrid contract, which refers to the combination of two or more contracts within a single transaction framework to achieve specific economic objectives. This study aims to analyze the concept of hybrid contracts, their implementation in Islamic banking, the benefits they provide, and the Sharia compliance challenges associated with their application. This research employs a qualitative approach using a library research method, drawing upon the Qur'an, Hadith, DSN-MUI fatwas, Islamic banking regulations, books, and relevant academic literature. The findings reveal that hybrid contracts are generally permissible in Islamic law as long as they do not contradict Sharia principles and each contract involved fulfills its respective legal requirements and conditions. The implementation of hybrid contracts in Islamic banking can be found in products such as murabahah bil wakalah, ijarah muntahiyah bittamlik (IMBT), and multi-service financing schemes. The use of combined contracts offers several advantages, including greater product flexibility, improved transaction efficiency, expanded financial services, and enhanced competitiveness of Islamic banks. However, their application also presents challenges, such as the potential presence of riba, gharar, legal stratagems (hilah), and the complexity of Sharia supervision. Therefore, the development of hybrid contract products requires transparent contract structures, effective supervision, and strict adherence to Sharia principles. This study concludes that hybrid contracts play a strategic role in supporting innovation and the growth of Islamic banking in the modern era, provided they remain aligned with the objectives of Sharia (maqashid al-shariah) and the principle of prudence.